La teología política. Un acercamiento a la teología fundamental de J. B. Metz. (2016)
As an essential task fundamental theology should “give reason for hope”, and as a basic element, that any fundamental theologian must take as his starting point, is the Revelation. It is also clear that this message the revelation conveys, has been presented with different shades according to the time and the historical characteristics of each author. We understand, then, that the effort of manualistic theology responded to the needs of its time; but in the course of history a particular way of understanding the revelation and dogma was surpassed; from there the progress achieved in this discipline since the Second Vatican Council, especially on how to address the issue of Revelation in the Dogmatic Constitution Dei Verbum, are understood.